Debt Relief and Beyond : Lessons Learned and Challenges Ahead - Primo Braga, Carlos A.; Domeland, Dorte (World Bank, 2012)
Heavily indebted low-income countries benefited from significant debt relief over the past decade. Under the Heavily Indebted Poor Countries (HIPC) Initiative and the Multilateral Debt Relief Initiative (MDRI), assistance of about $117 billion in nominal terms had been committed to 35 HIPC as of end-April 2009. This debt relief represents about half of the 2007 Gross Domestic Product (GDP) of these countries, whose debt burden is expected to drop by more than 80 percent once full debt relief is granted. As a result of relief already provided, debt-service payments have plummeted and expenditures on pro-poor growth programs increased. The book is divided into four parts. Part one examines the design of debt-relief initiatives and provides evidence of its effect on education, health, and economic growth. Part two describes the risks and opportunities developing countries face following debt relief. It identifies how they can safeguard debt sustainability; describes the role of sovereign risk for private sector access to capital; and draws lessons from the experience of market-access countries on the links between sovereign debt and development. Part three examines the concept and various policy proposals of dealing with 'odious' debt. Part four looks at debt management, debt restructuring, and the interplay between debt and fiscal policies. It provides guidance on debut sovereign bond issues; examines the issuance and management of sub-national debt; describes the challenges of crafting fiscal policy and managing debt and oil revenues in a (temporarily) oil-rich country (the Republic of Congo); and draws lessons from Chile's experiences using debt swaps in the 1980s.